2013
DOI: 10.1038/ncomms3439
|View full text |Cite
|
Sign up to set email alerts
|

Double perovskites as a family of highly active catalysts for oxygen evolution in alkaline solution

Abstract: The electronic structure of transition metal oxides governs the catalysis of many central reactions for energy storage applications such as oxygen electrocatalysis. Here we exploit the versatility of the perovskite structure to search for oxide catalysts that are both active and stable. We report double perovskites (Ln 0.5 Ba 0.5 )CoO 3 À d (Ln ¼ Pr, Sm, Gd and Ho) as a family of highly active catalysts for the oxygen evolution reaction upon water oxidation in alkaline solution. These double perovskites are st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

65
1,486
3
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,345 publications
(1,600 citation statements)
references
References 45 publications
(67 reference statements)
65
1,486
3
3
Order By: Relevance
“…In the following, we demonstrate that understanding the coupling between the dissolution of SRO(hkl) thin films and catalytic properties is essential to taking the next critical step-the selection of new materials that one would exhibit both optimal reactivity and stability. Therefore, beyond the question of reactivity of the SRO(hkl) films for the OER, a central issue of this work concerns stability-activity relationships that have been rarely discussed (at least not at atomic levels) in electrocatalysis on oxide surfaces, a notable exception being the recent work of Grimaud et al 50 on the double perovskites. Therefore, by exploring variations in the oxidation state of Ru active centres, the triggered dissolution of Ru cations via the electrode potential (resulting in formation of defect sites), and the concomitant evolution of O 2 on SRO(hkl) surfaces, much can be learned regarding a functional link between the oxidation state of active centres, their stability and their reactivity that is utterly inaccessible when studying high-surface area oxide materials.…”
Section: Resultsmentioning
confidence: 99%
“…In the following, we demonstrate that understanding the coupling between the dissolution of SRO(hkl) thin films and catalytic properties is essential to taking the next critical step-the selection of new materials that one would exhibit both optimal reactivity and stability. Therefore, beyond the question of reactivity of the SRO(hkl) films for the OER, a central issue of this work concerns stability-activity relationships that have been rarely discussed (at least not at atomic levels) in electrocatalysis on oxide surfaces, a notable exception being the recent work of Grimaud et al 50 on the double perovskites. Therefore, by exploring variations in the oxidation state of Ru active centres, the triggered dissolution of Ru cations via the electrode potential (resulting in formation of defect sites), and the concomitant evolution of O 2 on SRO(hkl) surfaces, much can be learned regarding a functional link between the oxidation state of active centres, their stability and their reactivity that is utterly inaccessible when studying high-surface area oxide materials.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of them are in a general ABO 3 formulation (A: rare earth or alkali metal ions; B: transition metal ions), in which the B site is usually recognized as catalytic active center. ORR and OER activities of perovskite oxides can be simultaneously improved by filling the surface B antibonding states of e g ‐orbital close to 1 and can be further increased by enhancing the covalence of B—O bond 207, 208. For example, Cho and co‐workers optimized the size of La x (Ba 0.5 Sr 0.5 ) 1− x Co 0.8 Fe 0.2 O 3− δ nanoparticles to adjust the catalytic activity for ORR and OER at the same time 209.…”
Section: Rechargeable Zn–air Batteriesmentioning
confidence: 99%
“…Double perovskite oxides were then later identified as a family of highly active catalysts for the OER with their activity being attributed to the computed O p-band centre being neither too close nor too far from the Fermi level. Grimaud et al 25 identified PBCO to have comparable activity to that of BSCF with enhanced stability towards surface modification during the OER measurements in alkaline electrolyte. Furthermore, Raabe et al 26 looked at a number of Mn-based double perovskites emphasizing the role of oxygen vacancies at the surface of the oxide on the OER activity.…”
mentioning
confidence: 99%